PPAR-γ, but not KCNJ11, Is Associated with Type 2 Diabetes Mellitus Progression among First-Generation Offspring of Lembak Ethnicity in Bengkulu, Indonesia - Dita, Diah Ayu Aguspa; Yunita, Elvira; Rizqoh, Debie; Ashan, Hesty Rhauda; Fahira, Dita (Althea Medical Journal, 2025)
Background: Genetic and environmental factors influence the onset and progression of type 2 diabetes mellitus (T2DM). Variants affecting peroxisome proliferator activated-receptor gamma (PPAR-γ) and potassium, inwardly rectifying channel subfamily J member 11 (KCNJ11) may alter insulin secretion and sensitivity. This study investigated the association between PPAR-γ and KCNJ11 gene expression and the risk of T2DM among first-generation (F1) offspring of T2DM patients of Lembak ethnicity in Bengkulu, Indonesia.Methods: A cross-sectional observational study was conducted from July to September 2024, recruiting 60 unrelated participants aged 18–40 years, all of whom were exposed to the neron tradition (high-sugar consumption). Gene expression of PPAR-γ and KCNJ11 was determined using real-time quantitative PCR (qRT-PCR).Results: F1 offspring of T2DM patients (n=30) had significantly (p<0.05) higher body weight (66.89±15.62 kg; p=0.008), body mass index (BMI) (23.55±3.46 kg/m2), HbA1C (6.55±1.25), random blood glucose levels (median 131 [75–371] mg/dl), and duration of neron consumption (median 3 [1–12] years) compared with controls (n=30). PPAR-γ expression differed significantly between group (1.60±2.91 vs 4.23±8.54; p=0.009), whereas KCNJ11 expression did not (0.79±0.76 vs 1.37±0.89; p=0.124). Multivariate analysis revealed no correlation between gene expression and the patients characteristic (p>0.05). Linear regression showed 30.4% of PPAR-γ and 45.8% of KCNJ11 variability.Conclusions: PPAR-γ expression is associated with T2DM onset among Lembak F1 offspring, whilst KCNJ11 expression is not. Multiple genetic and environmental factors likely contribute to disease progression. Screening for PPAR-γ expression may support interventions targeting insulin sensitivity and lipid metabolism.